2000
DOI: 10.1523/jneurosci.20-12-04745.2000
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Visual Attention Performance-Associated Prefrontal Neuronal Activity: Evidence for Cholinergic Modulation

Abstract: Cortical cholinergic inputs are hypothesized to mediate attentional functions. The present experiment was designed to determine the single unit activity of neurons within the medial prefrontal cortex (mPFC) of rats performing a sustained visual attention task. Demands on attentional performance were varied by the presentation of a visual distractor. The contribution of cholinergic afferents of the mPFC to performance-associated unit activity within this area was determined by recording neuronal activity before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(165 citation statements)
references
References 57 publications
(61 reference statements)
9
154
2
Order By: Relevance
“…Behavioral studies with experimental animals demonstrated that some neurotoxin lesions of the basal forebrain-cortical cholinergic system induced profound deficits of attentional processes in a five-choice serial reaction time task, and scopolamine, a muscarinic receptor antagonist, but not mecamylamine, a nicotinic receptor antagonist, impaired attentional processes. 9,[17][18][19][20] Thus these facts suggest that the cholinergic system, especially muscarinic receptors, may be essential for attention and arousal. The low dose (0.3 mg/kg) of methamphetamine significantly shortened the CRT, in agreement with the findings of a previous study.…”
Section: Discussionmentioning
confidence: 98%
“…Behavioral studies with experimental animals demonstrated that some neurotoxin lesions of the basal forebrain-cortical cholinergic system induced profound deficits of attentional processes in a five-choice serial reaction time task, and scopolamine, a muscarinic receptor antagonist, but not mecamylamine, a nicotinic receptor antagonist, impaired attentional processes. 9,[17][18][19][20] Thus these facts suggest that the cholinergic system, especially muscarinic receptors, may be essential for attention and arousal. The low dose (0.3 mg/kg) of methamphetamine significantly shortened the CRT, in agreement with the findings of a previous study.…”
Section: Discussionmentioning
confidence: 98%
“…There is some conflicting data on whether there is a significant cholinergic effect on sustained attention (Dalley et al, 2004;Gill et al, 2000;Grottick et al, 2003). The cholinergic system has a direct impact on EEG, with cholinergic activity in cortex being related to wakefulness and desynchronization of the EEG (Celesia and Jasper, 1966;Vanderwolf and Robinson, 1981).…”
Section: 22mentioning
confidence: 99%
“…The divided and/or sustained aspects of visual attention are thought to depend upon dorsal frontal cortical regions and the inputs of these structures to the striatum (Buchsbaum et al, 1990;Burk and Mair, 2001;Christakou et al, 2001;Gill et al, 2000;Muir et al, 1996;Passetti et al, 2000), while the initiation and selection of appropriate responses depend upon striatal circuitry and its modulation by dopamine (Brown and Robbins, 1989;Carli et al, 1985Carli et al, , 1989. In rodents and primates, there is no vasopressin input to these forebrain regions (Wang et al, 1997;Young et al, 1999), suggesting that the effects of vasopressin are indirectly mediated by other neuronal systems, such as monoaminergic and/or cholinergic nuclei (Boer et al, 1995;Caffe et al, 1985;Feenstra et al, 1990).…”
Section: Neural Circuitrymentioning
confidence: 99%